Unveiling Fiqh Munakahat in Mandailing Natal Pesantren: Exploring Gender Awareness and Women’s Marital Rights - Nasution, Suryadi; Hsb, Zuhdi; Akhyar (Edukasia Islamika : Jurnal Pendidikan Islam, 2025)
This study aims to examine how fiqh munakahat is taught in pesantren (Islamic boarding schools) and its implications for gender understanding and women’s rights in marriage. The research focuses on three pesantren in Mandailing Natal: Ma’had Darul Ikhlas, Pesantren Roihanul Jannah, and Ma’had Darul Ulum Muara Mais. Employing a qualitative approach with a multisite case study design, data were collected through participant observation, in-depth interviews, and document analysis. The findings reveal that the teaching of fiqh munakahat in these pesantren is still predominantly influenced by traditional interpretations, which tend to be patriarchal, with minimal discussion on women's rights. However, amidst this dominant narrative, seeds of transformation are emerging, particularly among the younger generation of pesantren students who are beginning to embrace progressive perspectives on gender. Resistance to modernity, limited intellectual capacity among instructors, and the influence of local culture present significant challenges to promoting gender equality. Nevertheless, advancements in information technology and the growing critical awareness among santri (students) offer substantial opportunities for reform. This study underscores the urgency for pesantren to incorporate gender perspectives into the fiqh munakahat curriculum as a step toward justice and equality. The research contributes to the literature on gender in Islam and pesantren education as agents of social transformation